Ação sinérgica de componentes da própolis sobre produção de citocinas e atividade bactericida de monócitos humanos - Cardoso, Eliza de Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Propolis is a natural product with several biological properties. It shows a very complex chemical composition, what may change according to the botanical sources. In the last decades researchers have focused on the activity of its components, in order to investigate their involvement in propolis action. However, little is known concerning the synergism of its constituents on the immune system. Thus, this work aimed to investigate whether the immunomodulatory effects of propolis on human monocytes are due to the interaction between three phenolic acids (caffeic, dihydrocinnamic and p-coumaric acid). Human monocytes were obtained from 10 healthy donors and incubated with such components and their combinations (cafeic+dihydrocinnamic; caffeic+p-coumaric; dihydrocinnamic+p-coumaric; and caffeic+dihydrocinnamic+pcoumaric) according to their concentrations in propolis composition, simultaneously or not with LPS. A possible cytotoxicity was assessed by the colorimetric MTT assay. After 18h incubation, supernatants were collected and the production of pro- and antiinflammatory cytokines (TNF-α and IL-10) was evaluated by enzyme-linked immunosorbent assay (ELISA). To evaluate the bactericidal activity, monocytes were incubated with components and challenged with Escherichia coli, and the percentage of bactericidal activity was calculated. Significant differences between treatments were determined by analysis of variance (ANOVA), followed by Dunnett's test (P<0.05). Without LPS, propolis and the associations between its acids stimulated the cytokines production. With inflammatory stimulus, the LPS-induce TNF-α and IL-10 production was maintained by propolis, its acids and their associations. Cinnamic acid increased IL-10 production and the bactericidal activity of monocytes, without affecting cell viability. These preliminary results suggest that these compounds may be involved in the immunomodulatory action of propolis, but further studies on the...

própolis é um produto natural que apresenta diversas propriedade biológicas. Esse apiterápico possui complexa composição química, que pode variar de acordo com as diferentes fontes botânicas utilizadas pelas abelhas. Nas últimas décadas, os grupos de pesquisa procuraram compreender a atividade de seus componentes, a fim de investigar seu envolvimento na ação da própolis. No entanto, há poucos estudos sobre o possível sinergismo de seus componentes no sistema imunológico. Assim, este trabalho buscou investigar se os efeitos imunomoduladores da própolis em monócitos humanos são devidos à interação entre três ácidos fenólicos (ácidos cafeico, dihidrocinâmico e p-cumárico). Para tal, monócitos humanos foram obtidos de 10 doadores saudáveis e incubados com os componentes isolados e suas combinações (cafeico+dihidrocinâmico; cafeico+p-cumárico; dihidrocinâmico+pcumárico; e cafeico+dihidrocinâmico+p-cumárico) de acordo com suas concentrações na composição da própolis, em ausência ou presença de LPS, por 18h. O possível efeito citotóxico foi avaliado após este período, pelo método colorimétrico de MTT. Após o período de incubação, os sobrenadantes foram coletados e a produção de citocinas pró- e anti-inflamatórias (TNF-α e IL-10) foi quantificada por ELISA. Para avaliar a atividade bactericida, as células foram incubadas com os componentes e, posteriormente, desafiadas com Escherichia coli. A porcentagem de atividade bactericida foi calculada e as diferenças significativas entre os tratamentos foram determinadas por análise de variância (ANOVA), seguida de teste de Dunnett (P<0,05). Em ausência de LPS, a própolis e as combinações entre seus ácidos estimularam a produção de citocinas. Em presença do estímulo inflamatório, a produção de citocinas induzida pelo LPS foi mantida pela própolis e pelas associações. O ácido dihidrocinâmico isolado aumentou a produção de IL-10 e a...
Synergistic action of propolis componentes on cytokines production and bactericidal activity of human monocytes
Keywords: Própole - Uso terapêutico; Citocinas; Monocitos; Fatores imunológicos; Própolis